2001
DOI: 10.1038/sj.onc.1204148
|View full text |Cite
|
Sign up to set email alerts
|

Tumor specific modulation of KU70/80 DNA binding activity in breast and bladder human tumor biopsies

Abstract: The Ku70/80 heterodimer is the regulatory subunit of the DNA-dependent protein kinase (DNA-PK) and its DNAbinding activity mediates DNA double-strand breaks repair. Although Ku80 was recently proposed as a caretaker gene involved in the control of genome integrity, no data are available on Ku70/80 DNAbinding activity in human tumors. Heterodimer DNAbinding activity and protein expression were assayed by electrophoretic-mobility-shift-assay (EMSA) and Western blot analysis, in nuclear and cytoplasmic extracts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
2
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 39 publications
3
69
2
1
Order By: Relevance
“…37 In fact, as the impairment of DNA repair process produces genetic instability and, in turn, cancer development, it has been suggested that Ku's loss-of-function induces tumorigenesis. [38][39][40] Conversely, its gain-of-function has been associated with hyperproliferation and evading apoptosis of different tumour histotypes. 41,42 On the basis of the results obtained in this work, it could be speculated that the above-mentioned resistance phenomena are related to a Ku-dependent dysregulation of Apaf1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…37 In fact, as the impairment of DNA repair process produces genetic instability and, in turn, cancer development, it has been suggested that Ku's loss-of-function induces tumorigenesis. [38][39][40] Conversely, its gain-of-function has been associated with hyperproliferation and evading apoptosis of different tumour histotypes. 41,42 On the basis of the results obtained in this work, it could be speculated that the above-mentioned resistance phenomena are related to a Ku-dependent dysregulation of Apaf1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to a proposed repair defect, many CIN tumors show upregulation of DSB repair pathways such as non-homologous end joining. 31,32 A related theory proposed the existence of a number of fragile sites on the chromosome. 30 Due either to the lack of repair or to an opening of the chromatin during active transcription, the chromosome would be more prone to rupture at specific sites.…”
Section: Are Aneuploidy and Chromosome Breakage Caused By A Cingle Mementioning
confidence: 99%
“…A continuous de novo generation of breaks, increasing in number with the complexity of translocations, explains why DSB repair is activated in many carcinomas. 31,32 Also telomerase appears to be involved in a general repair pathway that "heals" chromosomes after induction of DSB. 52 In accordance with the previous observation, telomerase reactivation in a hereditary breakage syndrome takes place only after cells have gone through crisis.…”
Section: Back To Bfbmentioning
confidence: 99%
“…But even though mutation of DSB repair genes results in DNA damage after irradiation, little effect was found in untreated cells (5,6). In addition, sporadic carcinomas bear few if any mutations in DSB repair genes, and many tumor samples show augmented instead of reduced repair activity (7,8). The role of DSB repair in de novo generation of structural defects thus remains uncertain.…”
mentioning
confidence: 99%